A novel modeling and simulation approach for the prediction of human thermophysiological comfort. Issue 5 (March 2021) - Awais, Muhammad; Krzywinski, Sybille; Wendt, Ellen
Thermophysiological comfort is one of the most important aspects of wear comfort. Currently, there are no software solutions available for the combined consideration of material physical and mechanical characteristics, fit, and thermophysiological behavior. Thus, a laborious empirical process is typically required to determine an appropriate design matching new textile materials to pattern cuts as well as changing climatic conditions. A detailed wear trial in a climatic chamber supports this process. The objective of this research is to analyze the thermal comfort of clothing with different thermal characteristics through the simulation of heat regulation in the human body, microclimate, clothing, and environment.